Design and synthesis of new inhibitors of p53–MDM2 interaction with a chalcone scaffold - Pereira, D (2019)
The virtual screening of a library of chalcone derivatives led us to the identification of potential new MDM2 ligands. The chalcones with the best docking scores obeying the Lipinski rule of five were subsequently prepared by base-catalyzed aldol reactions. The activity of these compounds as inhibitors of p53–MDM2 interaction was investigated using a yeast-based screening assay. Using this approach two chalcones (3 and 4) were identified as putative small molecule inhibitors of p53–MDM2 interaction. The activity of both chalcones was further investigated in a panel of human tumor cells. Chalcones 3 and 4 revealed a pronounced tumor cell growth inhibitory effect on tumor cell lines. Additionally, chalcone 4 caused alterations in the cell cycle profile, induced apoptosis and increased the levels of p53, p21 and PUMA proteins in NCI-H460 cells. Computational docking studies allowed to predict that, like nutlin-3A (a well-known small-molecule inhibitor of p53–MDM2 interaction), chalcones 3 and 4 bind to the p53-binding site of MDM2. The results here presented will be valuable for the structure-based design of novel and potent p53–MDM2 inhibitors.